The specifics of contractual relations in the oil and gas complex - O. V. Baykova; M. R. Tolstov (Вестник университета)
The key aspects of contractual relations in the oil and gas complex, which plays a crucial role in Russian economy, have been analyzed. The specifics of contractual relations in the oil and gas complex have been considered, due to the high level of capital intensity, long duration of project implementation, and a significant degree of government regulation. Special attention has been paid to the contracts classification (from contracts for exploration and production to agreements for transportation, infrastructure construction, and purchase and sale of oil and gas). Legal aspects of regulating contractual relations in the oil and gas sector, including state licensing, international law influence, as well as environmental and antitrust restrictions, have been examined. No less important issue related to the risk distribution mechanisms and parties’ responsibility, including the main risks in contractual relations and contract enforcement mechanisms, has been touched upon. The main types of risks have been given, including geological, technical, financial, economic, legal, and political, and practical recommendations for their minimization have been offered. Multistage dispute resolution mechanisms, including pre-trial regulation, mediation, and arbitration, which ensures stability and predictability of relations among market participants, have been studied.